2019
DOI: 10.14814/phy2.14048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical versus diet‐induced weight loss on appetite regulation and metabolic health outcomes

Abstract: Bariatric surgery is associated with significant and sustained weight loss and improved metabolic outcomes. It is unclear if weight loss alone is the main mechanism of improved metabolic health. The purpose of this trial was to compare indices of appetite regulation, insulin sensitivity and energy intake ( EI ) between participants achieving 10 kg of weight loss via Roux‐en‐Y Gastric Bypass ( RYGB ) or dietary restriction ( DIET ); intake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 65 publications
(67 reference statements)
4
25
1
Order By: Relevance
“…The DIOGENES sub-study reported no change in fasting Hunger, but the AUC Hunger decreased by 18% following LED intervention [ 54 ]. Following VLED interventions, Lyngstad et al [ 55 ] reported an increase in fasting Hunger and a decrease in postprandial Hunger, similar to our findings; Adam et al [ 56 ], Sumithran et al [ 57 ], and Nymo et al [ 58 ] reported no change in both fasting and postprandial Hunger; whereas Halliday et al [ 59 ] reported a decrease in fasting Hunger but an increase in postprandial Hunger. One likely explanation for the difference in appetite responses is the state of ketosis during the negative energy balance.…”
Section: Discussionsupporting
confidence: 89%
“…The DIOGENES sub-study reported no change in fasting Hunger, but the AUC Hunger decreased by 18% following LED intervention [ 54 ]. Following VLED interventions, Lyngstad et al [ 55 ] reported an increase in fasting Hunger and a decrease in postprandial Hunger, similar to our findings; Adam et al [ 56 ], Sumithran et al [ 57 ], and Nymo et al [ 58 ] reported no change in both fasting and postprandial Hunger; whereas Halliday et al [ 59 ] reported a decrease in fasting Hunger but an increase in postprandial Hunger. One likely explanation for the difference in appetite responses is the state of ketosis during the negative energy balance.…”
Section: Discussionsupporting
confidence: 89%
“…In some studies of weight loss from bariatric surgery [ 87 , 88 , 89 , 90 ] and CR from dietary intervention [ 91 , 92 ], plasma FFA concentration was reported to be lower after weight loss as compared to plasma from the same individuals before weight loss. In other longitudinal studies (also without weight-stable control groups), this decline of plasma FFA concentration with weight loss from bariatric surgery [ 25 , 93 ] or dietary intervention [ 93 ] was not observed. Results are mixed but seem to favor the likelihood of a reduced plasma FFA with weight loss.…”
Section: Modulation Of Plasma Ffa Concentration By Clinical Interventions and Lifestyle Factorsmentioning
confidence: 88%
“…One intriguing suggestion by the authors was that the elevated fat oxidation occurring from free fatty acid (FFA) utilization during (or after) exercise (2, 3) might lead to enhanced acetyl-CoA availability for use as a substrate for histone acetylation. Future work could lead to a greater understanding of the implications of elevated plasma FFA abundance and utilization during and after exercise (2,4) and in negative energy balance (5).…”
Section: Mechanisms Linking Transport and Utilization Of Metabolic Fuels To The Impact Of Nutrition And Exercise Upon Healthmentioning
confidence: 99%